2016
DOI: 10.1111/ejn.13407
|View full text |Cite
|
Sign up to set email alerts
|

Ventrolateral periaqueductal grey matter neurotransmission modulates cardiac baroreflex activity

Abstract: Baroreflex activity is a neural mechanism responsible for short-term adjustments in blood pressure (BP). Several supramedullary areas, which send projections to the medulla, are able to control this reflex. In this context, the ventrolateral part of the periaqueductal grey matter (vlPAG), which is a mesencephalic structure, has been suggested to regulate the cardiovascular system. However, its involvement in baroreflex control has never been addressed. Therefore, our hypothesis is that the vlPAG neurotransmiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…PAG neurons projecting to autonomic centers in the medulla are also involved in cardiovascular changes observed during opioid-dependent and independent endogenous analgesia ( Benarroch, 2006 ; Green et al, 2006 ). In addition, stimulation of the PAG alters baroreflex sensitivity and cardiac control ( Pelosi et al, 2007 ; Pereira et al, 2010 ; Benarroch, 2012 ; Lagatta et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…PAG neurons projecting to autonomic centers in the medulla are also involved in cardiovascular changes observed during opioid-dependent and independent endogenous analgesia ( Benarroch, 2006 ; Green et al, 2006 ). In addition, stimulation of the PAG alters baroreflex sensitivity and cardiac control ( Pelosi et al, 2007 ; Pereira et al, 2010 ; Benarroch, 2012 ; Lagatta et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…The dorsal motor vagus nucleus controls the excitability of the ventricles of the heart (Gourine et al, 2016). Additionally, in rats it has been shown that the PAG is involved in the modulation of heart rate and blood pressure (Lagatta et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, in rats it has been shown that the PAG is involved in the modulation of heart rate and blood pressure (Lagatta et al, 2016).…”
Section: The Involvement Of Androgen Receptors In Autonomic Functionsmentioning
confidence: 99%
“…For example, lipopolysaccharide (LPS) produces a hypertensive effect by inhibiting the adrenergic receptors in DPAG. VLPAG contains Ach, norepinephrine (NE), opioid receptors, and glutamate, which cause different BP and HR responses ( Lagatta et al, 2016 ). Microinjection of δ opioid receptor agonists into the VLPAG decreased the arterial pressure, while microinjection of glutamate into the VLPAG increased the cardiovascular responses in rats with normal BP and hemorrhagic hypotension; these effects were mainly mediated by NMDA receptors ( Alikhani et al, 2021 ).…”
Section: Main Functional Characteristics and Mechanisms Of Pagmentioning
confidence: 99%